From Pedagogy to Heutagogy: A Systematic Scoping Review of Digitalization of Pedagogies to Foster Self-Determined Learning (2010–2024) - Wickramasinghe, Vathsala (Innovations in Pedagogy and Technology, 2026)
The fourth industrial revolution technologies are primarily characterized by digitalization. Regardless of the underlying premise, i.e., pedagogical or andragogical, digitalization is the key to heutagogy. The present scoping review was conducted to 1) differentiate foundational learning paradigms of pedagogy, andragogy, and heutagogy as conceptualized in digital learning contexts, 2) classify digital technologies supporting digital learning, 3) classify digital platforms used in teaching and learning, 4) investigate drivers of technology-enhanced learning design in terms of financial support, infrastructure availability, and teacher preparedness, 5) investigate epistemological concerns arising from technology-enhanced learning design, and 6) investigate equity concerns of digital divide for learners from rural and low-bandwidth environments, as well as for female, disabled, and refugee learners. The scoping review followed the process of Arksey and O’Malley and aligned with PRISMA-ScR guidelines. The number of studies included in the review was 36. The findings suggest that the progression from pedagogy to heutagogy underscores the importance of digital technologies for self-directedness. The digital platforms redefine the boundaries of learning - where, when, and how learning occurs. However, this evolution remains uneven across contexts. Financial support, infrastructure availability, and teacher preparedness are decisive factors in digital transformations. The digital divide persists and constrains the realization of heutagogical potential by learners from rural and low-bandwidth environments, as well as by female, disabled, and refugee learners. Epistemologically, digital pedagogy is moving toward connectivism and co-created knowledge systems, challenging traditional notions of knowledge ownership, knowledge validation, authenticity, ethical governance, and learner assessment.